Persistent hiccups due to aripiprazole: a case report and review of the literature - Zhang, Yaoyin; Chen, Wei; Chen, Junming; Li, Mingmei; Huang, Yulan; Min, Wenjiao (Frontiers in Pharmacology, 2024)
Introduction: Aripiprazole, a commonly prescribed antipsychotic, has been rarely associated with the onset of hiccups. This study aims to elucidate the prevalence, risk factors, and management of aripiprazole-induced hiccups.We report a case of aripiprazole-induced hiccups in a 32-year-old male diagnosed with Somatic Symptom Disorder per DSM-5 criteria.A comprehensive literature review was conducted, identifying 29 case reports of aripiprazole-induced hiccups. Patient demographics, dosage, onset and duration of hiccups, and management strategies were analyzed.Results: Aripiprazole-induced hiccups predominantly affected adolescents and middle-aged male patients (86.7%). The majority of hiccups developed within 1-2 days post-prescription (90.9%) and resolved within 1-4 days after discontinuation of aripiprazole. Discontinuation of aripiprazole was the most effective management strategy (51.7%). Co-administration with benzodiazepines was identified as a significant risk factor.The findings suggest that clinicians should be vigilant for the onset of hiccups during the early stages of aripiprazole treatment, especially in male patients and those co-administered with benzodiazepines.Clinicians should be vigilant for hiccups during early aripiprazole treatment. Considering personality and psychological factors is crucial in managing hiccups in psychiatric patients.